Reminiscence therapy care program as a potential nursing intervention to relieve anxiety, depression, and quality of life in older papillary thyroid carcinoma patients: A randomized, controlled study - Chen, Li; Yang, Xianguang; Ren, Xiukun; Lin, Yufeng (Frontiers in Psychology, 2022)
Objective: Reminiscence therapy (RT) ameliorates psychological problems and quality of life in cancer patients. However, no study reports its effect on older papillary thyroid carcinoma (PTC) patients. This study intended to investigate the effect of the RT-care program (CP) on anxiety, depression, quality of life, and survival in older PTC patients. Methods: Eighty-six postoperative older PTC patients were enrolled and randomly assigned to RT-CP group (N=44) and usual (U)-CP group (N=42) as a 1:1 ratio for a 6-month intervention. Hospital Anxiety and Depression Scale (HADS) and Quality of Life Questionnaire-Core 30 (QLQ-C30) scores were assessed at baseline, month (M)1, M2, M4, and M6. Results: HADS and QLQ-C30 scores at baseline were not different between two groups. Additionally, HADS-anxiety score at M6 (P=0.029), and HADS-depression score at M2 (P=0.030), M4 (P=0.029), M6 (P=0.012) were reduced in RT-CP group versus U-CP group. Meanwhile, anxiety and depression rates from M1 to M6 were slightly decreased in RT-CP group versus U-CP group but did not reach statistical significance. Furthermore, depression severity at M6 was reduced in RT-CP group versus U-CP group (P=0.049). Besides, QLQ-C30 global health status was increased at M2 (P=0.023) and M6 (P=0.033), QLQ-C30 function score was elevated at M2 (P=0.040) and M4 (P=0.035), while QLQ-C30 symptom score was decreased at M2 (P=0.046) in RT-CP group versus U-CP group. Moreover, disease-free survival and overall survival were not different between two groups. Conclusion: RT-CP may be a potential intervention for ameliorating anxiety, depression, and quality of life in older PTC patients.